Transcriptomic and metabolic analyses reveal the potential mechanism of increasing steroidal alkaloids in Fritillaria hupehensis through intercropping with Magnolia officinalis - Duan, Yuanyuan; Liu, Xiaohong; Wu, Jiaqi; You, Jingmao; Wang, Fanfan; Guo, Xiaoliang; Tang, Tao; Liao, Mingyan; Guo, Jie (Frontiers in Plant Science, 2022)
Fritillaria hupehensis, a well-known medicinal perennial herb, is used as an antitussive and an expectorant. Continuous cropping and monoculture cultivation usually negativly affect the growth of F. hupehensis. Compared with the monoculture system, the F. hupehensis-Magnolia officinalis intercropping system significantly increases the yield of F. hupehensis. However, changes in steroidal alkaloid metabolites (the most important bioactive components) and their molecular regulatory mechanisms in F. hupehensis intercropping system remain unclear. We performed comparative transcriptomic and metabolomic analyses of F. hupehensis bulbs grown in monocropping and intercropping systems. A total of 40 alkaloids were identified, including 26 steroidal alkaloids, 4 plumeranes, 3 phenolamines, 1 pyridine alkaloid, and 6 other alkaloids. The results showed that intercropping significantly increased the levels of peimine, peiminine, hupehenine, korseveridine, verticinone N-oxide, delafrine, tortifoline, pingbeinone, puqienine B, puqienine E, jervine, ussuriedine, hydroxymandelonitrile, N-feruloylputrescine, and N-benzylmethylene isomethylamine in F. hupehensis, but decreased the levels of indole, p-coumaroylputrescine, and N-benzylformamide. Transcriptome sequencing identified 11,466 differentially expressed unigenes in F. hupehensis under the intercropping system, of which 5,656 genes were up-regulated and 5,810 genes were down-regulated. We proposed a possible steroidal alkaloid biosynthesis pathway, in which 12 differentially expressed genes were identified. The higher expressions of these genes in the intercropping system positively correlated with the high accumulation of peimine, peiminine, and hupehenine, further validating our proposal. Moreover, the biological processes of oxidative phosphorylation and plant hormone signal transduction, cytochrome P450 enzymes, ATP-binding cassette transporters, and transcription factors may play pivotal roles in the regulation of steroidal alkaloid biosynthesis. This study revealed the underlying molecular mechanisms of intercropping in improving steroidal alkaloids in F. hupehensis at the transcriptome and metabolome levels. These findings provided a theoretical foundation for sustainable development of this ecological planting method.